Studies of concentration dependence of the fluorescent quantum yield from rhodamine 6G and AuPd coreshell nanorods, using a response surface methodology - Ekkachai Rammarat; Kitsakorn Locharoenrat; Witoon Yindeesuk; Pattareeya Damrongsak (My University, 2017)
We have applied a response surface approach to study the fluorescence quantum yield (FQY) of rhodamine 6G (Rh6G) mixed with Au-Pd core-shell nanorods (Au-Pd NRs).The FQYs have been measured for the Rh6G concentrations varying from 3.53×10 -7 to 1.70×10 -6 mol/L and the concentrations of Au-Pd NRs from 7.06×10 -6 to 1.36×10 -4 mol/L.Our experimental results testify that the FQY depends notably on the proportions of Rh6G and Au-Pd NRs.A specific relationship between the FQY and the concentrations has also been confirmed by a response surface plot.It is found that the discrepancy between the experiment and the calculations is less than 2%.
Keywords: Rhodamine 6G; Nanorod; Quantum yield; Rhodamine; Nanocluster Synthesis and Applications